Conflitos interpessoais de idosas em instituição de longa permanência na perspectiva da equipe de enfermagem - Bruinsma, Jamile Lais (2016)
The long-term care institutions for the elderly are becoming one of the house source and support to the elderly in need of long-term care. Be admitted in these places has a great impact in the life of these people, which in addition to adapt to the routine, need also to establish new relationships and state their spaces. In these situations, conflicts between elderly residents or between them and professionals working at the institution may arise, which facilitates the occurrence of disharmonious conditions. Thus, situations that triggers conflicts and creates possible implications in daily life and health of institutionalized elderly are identified. This study has the main aim: to analyze the perception of the nursing team about the occurrence of relational conflicts of eldery in a long-term care institution. It is a qualitative study with 15 nursing professionals, that was conducted in March and July 2015 in an institution located in the central region of Rio Grande do Sul State. Data collecting was made using semi-structured interviews, recorded, transcribed and analyzed according to thematic content analysis of Minayo operative proposal. The ethical aspects of research involving human beings were respected following the Resolution 466/12 of the National Health Council. Conflict situations experienced by nurses and elderly of the institution, the aspects that led to these conflicts, and the management of nursing professionals at these situations were identified. Among the situations identified in this study, conflicts emerges in moments when the emotional and inclusion needs of elderly women were not met; when them try to preserve their identity and autonomy within the institution; and in situations where their behaviors are modified by the presence of psychological/psychiatric symptoms and have their attitudes contradicted by others. Factors that motivated the emergence of conflicts included attitudes from habits and the individuality created before the institutionalization and changes in behavior caused by neurological and / or psychiatric diseases. The performance of some professionals in an attempt to stop the conflicts are focused on authority, intimidation, punishment attitudes and the administration of medications. Other professionals have chosen to use conversation as an alternative for solving the conflicts. The results show that nursing professionals have difficulties for the management of relational conflicts of eldery that often come from the lack of skills of interpersonal relationships and knowledge about the specificities of fragile elderly population.